2011
DOI: 10.1007/s13142-011-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Supporting implementation of evidence-based behavioral interventions: the role of data liquidity in facilitating translational behavioral medicine

Abstract: The advancement of translational behavioral medicine will require that we discover new methods of managing large volumes of data from disparate sources such as disease surveillance systems, public health systems, and health information systems containing patientcentered data informed by behavioral and social sciences. The term "liquidity," when applied to data, refers to its availability and free flow throughout human/computer interactions. In seeking to achieve liquidity, the focus is not on creating a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A short introduction to data assets as a pathway to building high data liquidity is in [12]. How a liquid healthcare data system can facilitate managing large volumes of data from disparate sources is discussed in [13]. • Data Tokenization.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A short introduction to data assets as a pathway to building high data liquidity is in [12]. How a liquid healthcare data system can facilitate managing large volumes of data from disparate sources is discussed in [13]. • Data Tokenization.…”
Section: Related Workmentioning
confidence: 99%
“…We believe that a large part of the issues regarding data liquidity and exchange is partially a result of the lack of legal standardization, composability, and automation regarding legal agreements for data use, exchange, and access. Exemplars and parallels can be borrowed from the 13 Sec. VII-B1 14 Sec.…”
Section: Augmentation: Legal Aspects and Votingmentioning
confidence: 99%
“…30, 83 The EHR also provides the opportunity to expand knowledge about the patient for research purposes. 9798 Informatics, medicine and behavioral science experts are discussing the feasibility of including patient reports on psychosocial measures as part of the EHR. 49 In collaboration, NCI, the Office for Behavioral and Social Science Research and the Society of Behavioral Medicine have identified essential psychosocial constructs, such as diet, physical exercise, demographic characteristics, stress, depression and anxiety, and (brief) candidate instruments.…”
Section: Implications For Hit For Accelerating Discovery In Psycho-onmentioning
confidence: 99%
“…At the level of nationwide health care systems, eHealth technologies provide a substantial potential for cost control, cost savings, and rapid responses to public health emergencies [ 10 - 14 ]. Furthermore, researchers and industry representatives have been showing an increased interest in data liquidity being encouraged by the prospects of widely and securely available patient data; “big data” techniques may improve the cooperation and work flow between researchers and create innovation platforms for an exchange of ideas and, of course, real world health data [ 15 - 18 ].…”
Section: Introductionmentioning
confidence: 99%